Comparative study of the therapeutic effect of Doxorubicin and Resveratrol combination on 2D and 3D (spheroids) cell culture models - Barros, Andreia Sofia de Sousa (2018)
The assessment of drug-combinations for pancreatic cancer treatment is usually performed in 2D cell cultures. In this study, the therapeutic effect and the synergistic potential of a particular drug-combination towards 2D and 3D cell cultures of pancreatic cancer were compared for the first time. Thus, the effect of Doxorubicin:Resveratrol (DOX:RES) combinations (at molar ratios ranging from 5:1 to 1:5) in the viability of PANC-1 cells cultured as 2D monolayers and as 3D spheroids was analyzed. The results showed that the cells’ viability was more affected when DOX:RES combinations containing higher contents of RES (1:2–1:5 molar ratios) were used. This can be explained by the ability of RES to reduce the P-glycoprotein (P-gp)-mediated efflux of DOX. Further, it was also revealed that the synergic effect of this drug combination was different in 2D and in 3D cell cultures. In fact, despite of the 1:4 and 1:5 DOX:RES ratios being both synergistic for both types of PANC-1 cell cultures, their Combination Indexes (CI) in the monolayers were lower than those attained in spheroids. Overall, the obtained results revealed that the DOX:RES combination is promising for pancreatic cancer treatment and corroborate the emergent need to evaluate drug combinations in 3D cell cultures.